The Rotavirus Surveillance System in Yemen: Evaluation Study - Lardi, Eman Abdullah; Al Kuhlani, Sharaf Sharaf; Al Amad, Mohammed Abdullah; Al Serouri, Abdulwahed Abduljabar; Khader, Yousef Saleh (JMIR Publications, 2021)
BackgroundRotavirus (RV) kills over 185,000 children <5 years every year and is responsible for over one-third of all child diarrheal deaths worldwide. The Rotavirus Surveillance System (RVSS) in Yemen was launched in 2007 at five sentinel sites to monitor the impact of the vaccine on RV morbidity and mortality. ObjectiveThis study aimed to determine the usefulness of the RVSS, assess its performance, and identify the strengths and weaknesses of its implementation. MethodsThe Centers for Disease Control and Prevention's updated guidelines on evaluating a public health surveillance system were used to evaluate the RVSS. In this assessment, qualitative indicators, such as usefulness, flexibility, stability, simplicity, and acceptability, were assessed through in-depth interviews with stakeholders at the central level and semistructured questionnaires with the sentinel site coordinators. The indicators for quantitative attributes-sensitivity, positive predictive value (PPV), completeness, and timeliness-were assessed by reviewing the results of laboratory samples and a random sample of case report forms. The scores for the indicators were expressed as poor (<60%), average (60% to <80%), and good (≥80%). ResultsThe overall usefulness score of the RVSS was 73%, indicating an average rank. The RVSS was rated as having good flexibility (91%) and stability (81%), and average simplicity (77%) and acceptability (76%). In terms of quantitative attributes, the system was poor for sensitivity (16%), average for PPV (73%), and good for completeness (100%) and timeliness (100%). ConclusionsAlthough the system attributes were flexible, stable, capable of providing quality data, and performing timely data reporting, some attributes still needed improvements (eg, usefulness, simplicity, acceptability, and PPV). There is a need for a gradual replacement of donor funds with government funds to ensure sustainability. The RVSS in Yemen strongly requires a progressive increase in the number of sites in governorates and sensitivity enhancement.